Perancangan Risk Register dan Risk Response pada Proyek Feeder Resiliency Menggunakan Metode Kualitatif di PT. XYZ - Fadhilah, Syailsa; Tripiawan, Wawan; Yasa, Putu (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The feeder resilience project is a network development project in the form of feeders that can be restored effectively and efficiently by PT XYZ. The project has risks that can have an impact on several factors, namely productivity, performance, quality and changes in costs on the project. With this, there is a need for further risk analysis and design (risk register) to find out what risks will occur and know how to respond to risks (risk response) using a probability & impact matrix to determine the priority of risks that will occur. The method used is a qualitative method because it can create subjective design results based on real phenomena according to events in the field on projects by performing qualitative risk analysis. The risk identification that has been obtained will be assessed based on the probability of the risk occurring and the resulting impact including time, cost, quality, safety & security, and scope by relevant stakeholders and continued with determining the risk response that will be carried out. It was found that there were 175 risks that had been identified in the risk register with two types of risks, namely positive risks/opportunities and negative risks/threats and risk responses were determined to handle the risks.